Preoperative Factors Influencing the Results of Coronary Artery Bypass Grafting with Reduced Left Ventricular Myocardial Contractility - Rudenko, S. A.; Kaschenko, Y. V.; Klimenko, L. A.; Osipenko, N. S.; Rudenko, A. V.; Yuvchyk, O. V. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Myocardial infarction remains one of the most common causes of disability in patients. Prior myocardial infarction in 15–30% of cases leads to decrease in left ventricle (LV) contractility. Isolated drug therapy is ineffective in most cases – impressions of the coronary arteries require revascularization, including coronary artery bypass grafting. Data on the choice of optimal tactics in such patients is also limited. In addition, there is no consensus on the prognosis of mortality and management of this group of patients. Materials and methods. The study included 190 patients with the left ventricular ejection fraction (EF LV) of 35% or less, who underwent CABG at the National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine in the period from 01.01.2015 to 31.12.2018. The age of patients ranged from 29 to 83 years (61.13 ± 8.87). There were 170 men (89.47%) and 20 women (10.53%). Our data suggests that patients with low EF LV have complications typical of coronary artery bypass grafting, but the incidence of these complications is higher and increases with the EF LV decrease (except for the central nervous system (CNS) complications where there is no correlation). At the same time, such indicators as the duration of mechanical ventilation, the number of days of stay in the intensive care unit and the total number of days of stay in the hospital are increasing. The following complications most often arose in the postoperative period: acute heart failure, respiratory failure, renal failure. Based on our data, we came to the following conclusions: in patients with reduced LV myocardial contractility, the main complications after coronary artery bypass grafting were congestive heart failure, respiratory failure, renal failure and CNS complications. Among them, regardless of the level of EF LV, the most common were acute heart failure and complications of the respiratory system. The most significant factors of preoperative condition of patients with reduced LV myocardial contractility, which increase the risk of postoperative complications and increased mortality are: EF LV 30% and below, patient age over 60 years, creatinine rise to >200 mmol/L, pulmonary hypertension over 50 mmHg. Concomitant mitral regurgitation (moderate or severe) requires obligatory intraoperative correction.